Spoonerism in Primetime News headlines: an analysis of sound harmonization in Indonesian media - Muhardis (Cogent Social Sciences)
A spoonerism is a linguistic phenomenon that involves switching sounds between two or more words. Spoonerism is frequently used in the headlines of news articles, where it is employed to maintain sound harmony and grab readers’ attention. This study focuses on the spoonerism in the headlines of Primetime News on Metro TV, aiming to explore the different patterns and understandings of the phenomenon. We used critical discourse analysis as the primary method, and we collected the data from December 2022 to February 2023 from the website metrotvnews.com. The results show that twenty-one headlines use paired words with harmonious sounds, with eight different word combinations and seven distinct patterns of sound harmonization. The use of paired words with harmonious sounds in news headlines attracts the audience’s attention and adds appeal to the title. This research can provide valuable insights for media practitioners in crafting engaging news headlines and may open opportunities for further research on spoonerism in Indonesian-language news titles. Overall, this study offers an overview of the use of spoonerism in news headlines and its purpose, while also contributing to a better understanding of language and media.